2019
DOI: 10.1002/jsfa.9842
|View full text |Cite
|
Sign up to set email alerts
|

Fruit phytochemical composition and color parameters of 21 accessions of five Rosa species grown in North West Iran

Abstract: BACKGROUND The genus Rosa comprises economically important horticultural plants belonging to the family Rosaceae. Recently, the use of different Rosa species has increased owing to their multipurpose properties (ornamental, food and medicinal uses). In this study, 21 accessions of Rosa genotypes were compared for fruit phytochemical composition and color parameters. RESULTS The highest antioxidant activity (37.86 mg AAE g−1 FW) and total phenolic (8.17 mg GAE g−1 FW), total flavonoid (2.53 mg QUE g−1 FW), tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 76 publications
(192 reference statements)
2
35
0
Order By: Relevance
“…Total lycopene and β-carotene contents ranged between 4.00 μg g −1 (R. webbiana) and 26.80 μg g −1 FW (R. damascena) and between 1.02 μg g −1 (R. moschata) and 8.70 μg g −1 FW (R. canina), respectively. According the authors of this study, the variations of carotenoids level among the species of Rosa fruits could be attributed to species, climatic conditions, degree of maturation, and harvest time [27].…”
Section: Total Polyphenols Contentmentioning
confidence: 78%
“…Total lycopene and β-carotene contents ranged between 4.00 μg g −1 (R. webbiana) and 26.80 μg g −1 FW (R. damascena) and between 1.02 μg g −1 (R. moschata) and 8.70 μg g −1 FW (R. canina), respectively. According the authors of this study, the variations of carotenoids level among the species of Rosa fruits could be attributed to species, climatic conditions, degree of maturation, and harvest time [27].…”
Section: Total Polyphenols Contentmentioning
confidence: 78%
“…Its quantification declared that the availability of flavonoids in RPE and RRE were 1.22±0.06 μg QE/mg RPE and 0.59±0.03 μg QE/mg RRE, respectively. Shameh et al (2019) reported that the total flavonoid of R. canina was 2.53 mg QE/g FW. The flavonoid content of China rose 24.13 mg Catechin equivalent/g (Zheng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This data was in line with previous data that the petal of R. canina contained 776 QE mg/ml higher than fruit of R. canina 450 QE mg/mL (Moghaddam and Shaaban, 2018). Different Rosa genotypes contain rich phytochemical compounds that have significant variations in their levels (Shameh et al, 2019). Antioxidants are compounds that have the ability to neutralize or reduce the negative effects of free radicals, molecules that have unpaired electrons in an outer circle.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, the application of medicinal plant extracts and EOs has become known as a new and safe method to improve the quality stability and the shelf life of the samples [32,33]. According to Alirezalu et al [34] and Shameh et al [35], the findings of the antioxidant capacity of strawberries were related to phenolic compounds such as tannin, and TFC. Synowiec et al [36] evaluated the effects of Ocimum basilicum extract on apples.…”
Section: Antioxidant Activity By Dpph Assaymentioning
confidence: 99%